Maceió na guerra: o cotidiano da capital alagoana durante a segunda guerra mundial (1942-1943) - Fontes, Gigliele Pereira (2025)
The present work aims to discuss some aspects and developments of the Second World War, in the capital Maceió, in Alagoas. It starts from understanding the political of Interventoria Góis Monteiro and its strategies against the war to the impacts and transformations in the daily life of Maceió, from the blackout, carnival and sinking of the Merchant ship Itapagé. We understand, here, that the reading of these impacts of the war Will be carried out in its different spaces of experience in the capital. There fore, this research has as document Ary support, mainly, news papers (especially in the Hemerotecas of the Public Archive and the Historical and Geographical Institute of Alagoas), military memory books and Reports produced by Interventoria Góis Monteiro in the early 1940s. The historiographical dialogue is mediated by productions from Social Cultural History, Political Historyand Military History.